Pencarian Layout Keyboard dengan Travel Distance Terkecil Menggunakan Algoritma Genetik - Darmayasa, I Nengah Oka; Sanjaya ER, Ngurah Agus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 3 (2024): JELIKU Volume 12 No 3, February 2024, 2023)
Typing is an activity that is always carried out by several groups of people. One of the parameters of efficient typing is minimizing finger movement to type a letter, which is known as travel distance. The method that can be used to find the keyboard layout with the smallest travel distance efficiently is to generate the layout using a genetic algorithm. By using a genetic algorithm, each letter on the keyboard will act as a gene, the keyboard layout will act as a chromosome, and a collection of several keyboard layouts will act as a population. Each chromosome will be crossed with another chromosome by taking some genes from each chromosome and then combining them into a new chromosome. The method used to determine which chromosome is used for crossbreeding can use the travel distance of each chromosome. The smaller the travel distance, the more likely the chromosomes are to be crossbred. The most widely used keyboard today is still a keyboard with a layout called "QWERTY". When compared to typing Indonesian sentence data from TED-Multilingual-Parallel-Corpus, the QWERTY keyboard has a greater travel distance of around 9,311,735 compared to the keyboard layout obtained from the genetic algorithm method of 5,747.246, about 62% greater.